Ästhetik und Verkehr. - Wieland, Bernhard (Deutscher Verkehrs-Verl., 2008)
Der Streit um den Bau der Waldschlösschenbrücke in Dresden hat bundesweit Wogen geschlagen. Nachdem der Bau nunmehr begonnen hat und sich die Emotionen langsam abkühlen, scheint es an der Zeit, die Frage aufzuwerfen, ob aus dieser Debatte nicht auch etwas zu lernen sei.

The squabble over the Waldschlösschenbrücke in Dresden prompts us to think about the expansion of transport infrastructure facilities fairly soon being faced with aesthetic acceptance limitations. The most important lesson to be learnt from the Dresden debate is that, in view of the ever more closely integrate transport infrastructure facilities aesthetic aspects are likely to play a greater role in future. It would therefore make sense to think about how aesthetic aspects could be brought more into transport infrastructure-related profit and cost analysis. Is this actually possible or desirable in the case of such a subjective matter as 'beauty'? This commentary attempts provide an impetus for deliberations.
Aesthetics and transport.
Keywords: Verkehr; Verkehrsplanung; Verkehrsbauwerk; Landschaftseinbindung; Kulturlandschaft; Brücke; Verkehrsinfrastruktur; Fremdenverkehr; Mobilität; Kosten-Nutzen-Analyse; Architektur; Städtebau; Monetarisierung